125m-75m+43875=46125-175m

Simple and best practice solution for 125m-75m+43875=46125-175m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 125m-75m+43875=46125-175m equation:


Simplifying
125m + -75m + 43875 = 46125 + -175m

Reorder the terms:
43875 + 125m + -75m = 46125 + -175m

Combine like terms: 125m + -75m = 50m
43875 + 50m = 46125 + -175m

Solving
43875 + 50m = 46125 + -175m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '175m' to each side of the equation.
43875 + 50m + 175m = 46125 + -175m + 175m

Combine like terms: 50m + 175m = 225m
43875 + 225m = 46125 + -175m + 175m

Combine like terms: -175m + 175m = 0
43875 + 225m = 46125 + 0
43875 + 225m = 46125

Add '-43875' to each side of the equation.
43875 + -43875 + 225m = 46125 + -43875

Combine like terms: 43875 + -43875 = 0
0 + 225m = 46125 + -43875
225m = 46125 + -43875

Combine like terms: 46125 + -43875 = 2250
225m = 2250

Divide each side by '225'.
m = 10

Simplifying
m = 10

See similar equations:

| 2x+3(-8)=0 | | 15x-2.4x=0.6+7.6x | | -4(x)-2y=-12 | | 25p^2-4=0 | | 5x=40*0.5 | | a=h(b+c)solve(b) | | 2x+5(x-1)= | | 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 | | 9s-36=5s | | 64g^3-125h^3=0 | | 13(x-4)=8x-32 | | 16t^2=-h+100 | | 3/4+1/4x=3/4x-1/4 | | -4=3n-7n | | 2x-60=x | | x-2=14*2 | | 16t^2+h=100 | | 1-11-3x=32 | | x+by=c*x | | (2m-7)squared= | | 2(7)-2x=6 | | 12x-4(3x)=0 | | 4b-8b^2=0 | | x/2-1/5=x/3+1/4 | | Y+5/8=-2 | | -17x=391 | | 7y-18=-46+3y | | 6(1)-10x=77 | | 2x-5(x-2)=-6+3x-20 | | -6(8+5n)-5=6n+19 | | (8xy-y)(8xy-y)= |

Equations solver categories